Is preoperative genicular radiofrequency ablation effective for reducing pain following total knee arthroplasty? A pilot randomized clinical trial. Issue 9 (2nd July 2021) - Mishra, Puneet; Edwards, David; Huntoon, Marc; Sobey, Christopher; Polkowski, Gregory; Corey, John; Mishra, Kelly Louise; Shinar, Andrew; Engstrom, Stephen; Palmer, Cassandra; Bruehl, Stephen
Abstract : Background and objective: Although total knee arthroplasty (TKA) is an effective treatment for severe knee osteoarthritis (OA), a subset of patients experience significant postoperative pain and dissatisfaction. Several clinical trials support the analgesic benefits of genicular nerve radiofrequency ablation (GN-RFA) for non-operative knee OA, but only one prior trial has examined the effects of this intervention given preoperatively on postoperative outcomes following TKA, showing no analgesic benefit of cooled GN-RFA. The current study evaluated whether conventional thermal GN-RFA performed preoperatively resulted in significant improvements in pain and function following TKA. Methods: This was a single-center, prospective, randomized, sham-controlled, double-blinded pilot trial in which patients received either conventional GN-RFA (n=30) or sham (n=30) between 2 and 4 weeks prior to their TKA. Baseline measures were obtained preprocedurally on the day of intervention, with follow-up outcomes obtained preoperatively on the day of surgery, and at 2 and 6 weeks postoperatively. Results: Patients receiving GN-RFA showed no significant improvements relative to sham controls in the primary outcome, pain intensity at rest at 6-week follow-up. Secondary outcomes, including pain with ambulation and physical function, also showed no significant differences between groups at any follow-up assessment. Conclusions: Conventional GN-RFA of the superior lateral, superior medial, and inferior medial genicular nerves when performed prior to TKA did not provide clinically significant pain relief or improvement in functional status at 2 or 6 weeks postoperatively. Trial registration number: NCT02947321 .